Studying the Atomic and Molecular Hydrogen Mass (MHI, MH2) Properties of the Extragalactic Spectra - Al Najm, M. N. (Iraqi Journal of Science, 2020)
The purpose of this study is to deal with dust and interstellar molecular and atomic gas owing to obtaining a proportion of cold gas to dust and to understand the characteristics of the molecular gas in extragalactic data selected from the Herschel SPIRE/ FTS archive. The physical properties of a sample of 65 extragalactic spectra characterized by the activity of star formation were discussed in this work. Statistical analyses, using STATISTICA program, were made for the content of cold gas (MHI, MH2), dust mass (Mdust), cold temperature of dust (Td) and luminosities in Far-infrared to CO line radiations, while coefficients of partial correlation within those characteristics were established. The results showed that the molecular hydrogen mass (MH2) is strongly correlated with the HI or the total gas mass corresponding to the Far-infrared emission (LFIR) resulting from dust in the galaxies molecular clouds. The results also indicated that these kinds of galaxies have large molecular mass as well as high star formation efficiency per unit mass.